2011
DOI: 10.4330/wjc.v3.i5.153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence of interaction between clopidogrel and proton pump inhibitors

Abstract: Clopidogrel is approved for reduction of atherothrombotic events in patients with cardiovascular (CV) and cerebrovascular disease. Dual antiplatelet therapy with aspirin and clopidogrel decreases the risk of major adverse cardiac events after acute coronary syndrome or percutaneous coronary intervention, compared with aspirin alone. Due to concern about gastrointestinal bleeding in patients who are receiving clopidogrel and aspirin therapy, current guidelines recommend combined use of a proton pump inhibitor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The significance mentioned is, 'the individual patient's risk factors for gastrointestinal bleeding should be considered against the possible risk of an interaction with clopidogrel, to consider the use of an alternative antiplatelet agent free of interaction with proton pump inhibitors, if their use is essential.' Lin et al in their study suggested a recommendation to separate these two drugs with a gap of 12-15 h to prevent any competitive inhibition and suggested taking PPI before breakfast and clopidogrel at bedtime [16].…”
Section: Discussionmentioning
confidence: 99%
“…The significance mentioned is, 'the individual patient's risk factors for gastrointestinal bleeding should be considered against the possible risk of an interaction with clopidogrel, to consider the use of an alternative antiplatelet agent free of interaction with proton pump inhibitors, if their use is essential.' Lin et al in their study suggested a recommendation to separate these two drugs with a gap of 12-15 h to prevent any competitive inhibition and suggested taking PPI before breakfast and clopidogrel at bedtime [16].…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole decreases the effect of clopidogrel by inhibiting the hepatic enzyme CYP2C19 metabolism, and thus decreasing the formation of the active antiplatelet metabolite. 17,24 Pantoprazole 25 and famotidine 26 can be alternatives to omeprazole to be used with clopidogrel.…”
Section: Inappropriate Prescribingmentioning
confidence: 99%
“…In addition, overuse of these medications for nonindicated conditions is prevalent [12,13]. These medications are generally well tolerated and have traditionally been considered relatively safe and free from adverse effects; although more recently, there have been reports linking PPIs with Clostridium difficile-associated diarrhea, hypomagnesemia, increased cardiovascular events in cardiac patients on clopidogrel, and pneumonia [14][15][16][17]. Due to the high prevalence of PPI use and the impact of osteoporosis-related fractures on health and quality of life, evidence of even a moderate association between these medications and fragility fractures would have important health implications.…”
Section: Introductionmentioning
confidence: 99%